Relationship Economic Growth with Foreign Direct Investment - Prince Charles Heston Runtunuwu (AIBPM Publisher, 2020)
This study aims to determine the one-way causality relationship between foreign investment and economic growth, a one-way causality relationship between economic growth and foreign investment, and a two-way causality relationship between foreign investment and economic growth in Indonesia. This was conducted in Indonesia, the data are secondary data taken using the method time series from 1971 to 2018 from the official websites, the Investment Coordinating Board, and literature sources, Foreign Investment and Gross Domestic Product. (1) in the long run the Economic Growth variable has a significant effect on Foreign Direct Investment, and vice versa; and (2) the Foreign Direct Investment variable has a significant effect on Economic Growth; (3) in the short term, the Economic Growth variable has an influence on Foreign Direct Investment, and vice versa; and the Foreign Direct Investment variable has an influence on Economic Growth. It is possible to have a better long-term relationship, bringing positive impact on economic growth in Indonesia when investment in Indonesia increases. Conversely, when economic growth decreases, it means that foreign investment is also low. Granger Causality test, shows a two-way causality relationship between Economic Growth and Foreign Direct Investment and vice versa. It is necessary to maintain growth to attract foreign direct investment, as well as foreign investment. Investment climate needs to be improved enabling to invest in Indonesia.